Abordagem de saúde sexual por enfermeiras no contexto da Atenção Primária à Saúde - Iracy Sofia Barbosa (2021)
Introduction: The right to sexual health was a historic achievement of humanity. Among the Sustainable Development Goals, in the UN's 2030 Agenda, is universal access to sexual and reproductive health care services. To achieve this goal, Primary Health Care (PHC) has a recognized role. However, other publications describe that the actions offered in PHC are almost always focused on reproductive demands, making sexual demands invisible or restricted to addressing Sexually Transmitted Infections. Nurses, as part of the Family Health Teams (FHS) and co-responsible for coordinating the reception and management of care in the PHC, must include sexual health in their care. However, studies show these professionals' difficulties in addressing sexuality in their care routines. Aims: 1) Knowing the needs and problems related to the sexual health of PHC users in the city of Belo Horizonte, according to the users themselves; 2) Identify the perception of the FHS nurses in the municipality about the needs and problems related to the users' sexual health and how they address these demands; 3) Knowing the current scenario of the municipality in relation to the needs and problems of users and the approach to sexual health adopted by the nurses of the FHS, based on the integration of quantitative and qualitative data. Method: This is a study of mixed methods of the convergent parallel type. The qualitative approach, based on John Gagnon's Theory of Sexual Scripts and carried out through in-depth interviews, had priority in the study. We analyzed the participants' speeches through the Structural Analysis of Narrative. The sample consisted of 22 participants, 13 users and nine nurses. The nurses were chosen by drawing lots, one from each district in the municipality. Users were defined part by draw and part by snowball, necessary to ensure greater gender diversity among participants. The quantitative approach consisted of a descriptive cross-sectional survey carried out through online forms, distributed to nurses from the FHS in the municipality through WhatsApp groups and e-mails from health centers in Belo Horizonte. The final study population consisted of 210 nurses, which corresponded to 35.7% of the total number of FHS nurses in the city. The analysis was carried out through the calculation of proportions and Pearson's chi-square test with a significance level of 5%. Results: The needs and problems related to the sexual health of PHC users are structured in cultural, interpersonal and intrapsychic dimensions and concern the experience of relationships and pleasure in a context of sexism and gender inequality, permeated by the taboo that still contributes to the silencing of people's intimacy. This can result in emotional suffering and/or life adjustments in a way that does not prioritize sexual pleasure. Most of the time, these needs are not perceived by health professionals in their care, since their approaches prioritize the biological model over the body and life of users. Among the 91.4% of nurses interviewed in the quantitative study who stated that they approach sexual health in the consultations, 48.7% do so only a few times. According to 75.1% of nurses, users have few demands, which can ensure some comfort by keeping the focus on symptoms and physical complaints, perpetuating the invisibility of individuals' sexuality. There was convergence of results found in the different methods. Conclusion: Sexual health must be understood and included in PHC actions in order to achieve comprehensive care. Recognizing the importance of sexual scripts for care, especially when they are dysfunctional for the lives of users, and acting, helping them to build new scripts that allow them to access a healthy sexual life, must be part of the approach to health with a focus on sex education. In this sense, it is urgent to invest in the training of PHC professionals to equip them to approach sexual health.